Does rTMS reduce depressive symptoms in young people who have not responded to antidepressants?. Issue 5 (10th October 2018) - Rosenich, Emily; Gill, Shane; Clarke, Patrick; Paterson, Tom; Hahn, Lisa; Galletly, Cherrie
Abstract : Aim: Depression is common in young people, and there is a need for safe, effective treatments. This study examined the efficacy of repetitive transcranial magnetic stimulation in a sample of young people aged 17 to 25 years. Methods: This retrospective study included 15 people aged 17 to 25 years referred by their private psychiatrists affiliated with Ramsay Health Care, South Australia Mental Health Services. All patients met Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria for treatment‐resistant Major Depressive Disorder. Eleven patients received right unilateral treatment and four patients received bilateral treatment. Patients were assessed at baseline and after treatment. Results: There was a significant improvement on the Hamilton Rating Scale for Depression ( t (14) = 4.71, P < 0.0001); Montgomery‐Åsperg Depression Rating Scale ( t (14) = 3.96, P < 0.01) and the Zung Self‐Rating Depression Scale ( t (14) = 4.13, P < 0.01). There was no difference in response by gender or age. The response rates in these young people did not differ significantly from those of adults aged 25 to 82 years. Conclusion: This open label, naturalistic study suggests that repetitive transcranial magnetic stimulation is an effective treatment in young adults who have treatment‐resistant depression. Randomized sham‐controlled studies are needed to further investigate the efficacy of this treatment in this age group.